Structural proteins of Kaposi's sarcoma-associated herpesvirus antagonize p53-mediated apoptosis - Chudasama, Priya; Konrad, A.; Jochmann, R.; Lausen, Berthold; Holz, Patrick; Naschberger, Elisabeth; Neipel, Frank; Britzen-Laurent, Nathalie; Stürzl, Michael (Oncogene, 2015)
The tumor suppressor p53 is a central regulatory molecule of apoptosis and is commonly mutated in tumors. Kaposi's sarcoma-associated herpesvirus (KSHV)-related malignancies express wild-type p53. Accordingly, KSHV encodes proteins that counteract the cell death-inducing effects of p53. Here, the effects of all KSHV genes on the p53 signaling pathway were systematically analyzed using the reversely transfected cell microarray technology. With this approach we detected eight KSHV-encoded genes with potent p53 inhibiting activity in addition to the previously described inhibitory effects of KSHV genes ORF50, K10 and K10.5. Interestingly, the three most potent newly identified inhibitors were KSHV structural proteins, namely ORF22 (glycoprotein H), ORF25 (major capsid protein) and ORF64 (tegument protein). Validation of these results with a classical transfection approach showed that these proteins inhibited p53 signaling in a dose-dependent manner and that this effect could be reversed by small interfering RNA-mediated knockdown of the respective viral gene. All three genes inhibited p53-mediated apoptosis in response to Nutlin-3 treatment in non-infected and KSHV-infected cells. Addressing putative mechanisms, we could show that these proteins could also inhibit the transactivation of the promoters of apoptotic mediators of p53 such as BAX and PIG3. Altogether, we demonstrate for the first time that structural proteins of KSHV can counteract p53-induced apoptosis. These proteins are expressed in the late lytic phase of the viral life cycle and are incorporated into the KSHV virion. Accordingly, these genes may inhibit cell death in the productive and in the early entrance phase of KSHV infection.
EVALuna2:8221